Penerapan Algoritma Punctured Elias Code pada Aplikasi Kamus Besar Bahasa Indonesia (KBBI) Berbasis Android - Zulkhairia, Zulkhairia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The large Indonesian dictionary has a large size because the quality of the resulting dictionary is better, so the file size needed for it is getting bigger. And the compression process is needed to reduce the file capacity to be smaller in order to save on the use of storage space. With a relatively large data size, during the data transfer process it can fail because the storage media does not have enough space. By performing the compression process on the large Indonesian dictionary, a process can be carried out to reduce the size of the data by reducing the bits in the large Indonesian dictionary, making it easier to carry out a data transfer process effectively. The procedure for compressing the large Indonesian dictionary (KBBI) starts from selecting the large Indonesian dictionary to be compressed, then the book will be compressed with the punctured Elias code algorithm so as to produce a compressed book that has a smaller size.2. The implementation of the punctured Elias code algorithm for compression of the Big Indonesian Dictionary (KBBI) is done by reading the hexadecimal value from a Big Indonesian Dictionary (KBBI), then changing the hex value into a new bit value in the form of a binary number, then rearranging the binary value into new character. Where the compression results are based on the ratio of 32% based on 80 bit data samples with 25 Bit compression results